Berberine Improves Glucose and Lipid Metabolism in HepG2 Cells Through AMPKα1 Activation - Ren, Gang; Guo, Jiang-Hong; Qian, Yu-Zhen; Kong, Wei-Jia; Jiang, Jian-Dong (Frontiers in Pharmacology, 2020)
Aim This study is designed to investigate whether or not AMP-activated protein kinase α1 (AMPKα1) is required for natural product berberine (BBR) to improve glucose and lipid metabolism in HepG2 cells. Methods AMPKα1 knocked-out (KO, AMPKα1-/-) cells were obtained by co-transfection of the CRISPR/Cas9 KO and HDR (homology-directed repair) plasmid into HepG2 cells, as well as subsequent screen with puromycin. The expression levels of target proteins or mRNAs were determined by western blot or real-time RT-PCR, respectively. Cellular AMPK activity, glucose consumption, lactate release, glucose production, and lipid accumulation were determined by kits. Results The results showed that the AMPKα1 gene was successfully KO in HepG2 cells. In AMPKα1-/- cells, the protein expression of AMPKα1 and phosphorylated-AMPKα1 (p-AMPKα1) disappeared, the level of total AMPKα declined to about 45–50% of wild type (p < 0.01), while p-AMPKα level and AMPK activity were reduced to less than 10% of wild type (p < 0.001). BBR increased p-AMPKα1, p-AMPKα, AMPK activity, and stimulated glucose consumption, lactate release, inhibited glucose production in wild type HepG2 cells (p < 0.05 or p < 0.01). BBR also reduced intracellular lipid accumulation and suppressed the expression of lipogenic genes in oleic acid (OA) treated wild type HepG2 cells (p < 0.05 or p < 0.01). In AMPKα1-/- HepG2 cells, the stimulating effects of BBR on p-AMPKα1, p-AMPKα, AMPK activity, and its improving effects on glucose and lipid metabolism were completely abolished. Conclusion Our study proves that AMPKα1 plays a critical role for BBR to improve glucose and lipid metabolism in HepG2 cells. Our results will provide new information to further understand the molecular mechanisms of BBR.